Native and non-native winter foraging resources do not explain Pteropus alecto winter roost occupancy in Queensland, Australia - Baranowski, Kelsee; Bharti, Nita (Frontiers in Ecology and Evolution, 2024)
Anthropogenic land use change concurrent with introductions of non-native species alters the abundance and distribution of foraging resources for wildlife. This is particularly concerning when resource bottlenecks for wildlife are linked to spillover of infectious diseases to humans. Hendra virus is a bat-borne pathogen in eastern Australia. Spillovers align with winter food shortages for flying foxes and flying foxes foraging in agriculture or peri-urban lands, as opposed to native forests. It is believed the increased abundance and spatiotemporal reliability of non-native species planted in anthropogenically modified areas compared to native, ephemeral diet species may be a key draw for flying foxes into urban and peri-urban areas. We investigate the explanatory power of environmental factors on the winter roost occupancy of the reservoir for Hendra virus, the black flying fox Pteropus alecto, from 2007-2020 in Queensland, Australia. We measured the extent, spatial aggregation, and annual reliability of typical (i.e. native) and atypical (i.e. non-native) winter habitat species in 20km foraging areas around roosts surveyed by the National Flying Fox Monitoring Program. We find that neither the extent nor the spatial distribution of winter habitats explained black flying fox winter roost presence. Although the establishment of roosts was associated with high reliability for typical winter diet species, the reliability of frequently listed winter diet species surrounding surveyed roosts was not different between roosts that were occupied versus unoccupied in the winter. Significant interactions between lagged weather conditions and winter habitats identified by the best model did not reflect observable differences in patterns of occupancy upon scrutiny. Static measures of winter habitat and weather conditions poorly explained the winter roost occupancy of black flying foxes. Understanding the drivers of flying fox movement and presence requires further investigation before they can be thoughtfully integrated into Hendra spillover prevention efforts and flying fox management.